1998
DOI: 10.1007/s000110050316
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of JTE-522, a novel prostaglandin H synthase-2 inhibitor, on adjuvant-induced arthritis and bone changes in rats

Abstract: These results suggest that JTE-522 possesses potent anti-arthritic activities and suppressive activity on inflammatory bone resorption without gastric side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…(31,32) In this study, the same range of dosage (0.3-10 mg/kg/ day) was applied to AIA rats for all drugs, which were decided according to previous reports on their antiinflammatory potencies in the same model. (33)(34)(35) This range of dosage was also determined to cover their clinical daily dosages: 4 mg/kg for celecoxib, 0.5 mg/kg for rofecoxib, 2-5 mg/kg for JTE-522, and 5 mg/kg for acetazolamide. Although the dosage of rofecoxib seems about 1/10 of those of other drugs, gastrointestinal absorption of this drug in rats is reported to be about 1/10 that in humans, (36,37) suggesting that these drugs of the same dosage have similar biological potencies in AIA rats.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…(31,32) In this study, the same range of dosage (0.3-10 mg/kg/ day) was applied to AIA rats for all drugs, which were decided according to previous reports on their antiinflammatory potencies in the same model. (33)(34)(35) This range of dosage was also determined to cover their clinical daily dosages: 4 mg/kg for celecoxib, 0.5 mg/kg for rofecoxib, 2-5 mg/kg for JTE-522, and 5 mg/kg for acetazolamide. Although the dosage of rofecoxib seems about 1/10 of those of other drugs, gastrointestinal absorption of this drug in rats is reported to be about 1/10 that in humans, (36,37) suggesting that these drugs of the same dosage have similar biological potencies in AIA rats.…”
Section: Figmentioning
confidence: 99%
“…Accumulated evidence has also shown the bonesparing effects of COX-2 inhibitors using mouse and rat models in vitro and in vivo. (10,34,(44)(45)(46)(47) Because both COX-2 and CAII show 80-90% homologies in nucleotides and amino acids among mice, rats, and humans, (48)(49)(50) these results may be applicable to humans. For the clinical application of COX-2 selective agents as a treatment of bone resorptive disorders including RA, however, we should be cautious not only with cardiovascular events above, but also with possible inhibition of bone repair and ingrowth that has recently been reported in animal models when administered for a long period of time.…”
Section: Figmentioning
confidence: 99%
“…We have previously reported that JTE-522 does not inhibit COX-1 activity at a concentration of 100 mM in vitro, but shows 1100 times higher selectivity for COX-2 than for COX-1 [13]. Furthermore, JTE-522 does not induce gastric lesions after 30 mg/kg daily oral administration for 24 days [15]. In contrast, indomethacin shows lower selectivity for COX-2 and produces gastric lesions at 1 and 3 mg/kg, p.o.…”
Section: Discussionmentioning
confidence: 91%
“…[13][14][15]. We predicted that JTE-522 exerts its anti-inflammatory activity by selective inhibition of COX-2 at sites of inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation